In vitro effect of Callistemon viminalis and Melaleuca cajuputi ethanolic extracts as botanical fungicide and insecticide - Somnuek, S.; Thipmanee, K.; Jaenaksorn, T. (International Journal of Agricultural Technology, 2021)
Effect of ethanolic extracts of Callistemon viminalis (EECV) and Melaleuca cajuputi (EEMC) leaves was evaluated in laboratory against plant pathogenic fungus (Alternaria sp.) and plant insect pests (Aphis craccivora and Phenacoccus manihoti). Regarding the study on botanical fungicide, the combined formulas of EECV and EEMC (5000 ppm) in ratios of 100:0, 75:25, 50:50, 25:75 and 0:100 were tested on mycelial growth and spore germination of tested fungus. The results revealed that all tested formulas of plant extracts gave significant inhibition on mycelial growth and spore germination in the ranges of 27.5-92.7% and 75-100%, respectively. However, the EEMC itself was unexpectedly found highly effective than the combined formulas. In the case of insecticidal activity, the preliminary experiment of EECV and EEMC (2000, 10000 and 20000 ppm) was performed on aphid and mealybug. The result presented that all concentrations of EECV and EEMC significantly showed the mortality effect on aphid and mealybug about 5-100%. In addition, the EECV and EEMC at 2000 and 10000 ppm showed a repellency of about 5-55%. Then, both plant extracts at 2500, 5000, 10000 and 20000 ppm concentrations were tested to those insects. The 100% mortality of aphid and mealybug was found in the highest concentration of EECV and EEMC while 2500-10000 ppm concentrations showed in the range of 38-98%. The 100% repellency capacity was observed at 10000 ppm concentration. Therefore, two Myrtaceae ethanolic extracts are promising to be used as a natural pesticide in controlling Alternaria and insect pests in laboratory.